The correlation between level of racial microaggression and communication approach of filipinos in Oahu, Hawaii - Tuzon, Jezrell Armada (College of Arts and Letters, University of the Philippines Diliman, 2019)
This thesis focused on Filipinos residing in Oahu, Hawaii and their communication approaches when faced with racial microaggression. Through Co-Cultural Theory (CCT) and Racial and Ethnic Microaggression Scale (REMS) the researcher was able to fulfill the following objectives:1) To identify level of racial microaggression experienced by Filipinos in Oahu, Hawaii;2) To identify the communication approaches used by Filipinos as part of minority group in Oahu, Hawaii; and 3) To determine the correlation between racial microaggression and communication approach of Filipinos in Oahu, Hawaii. The findings of this study showed that male Filipinos respond to racial microaggression through aggressive and assertive communication approach while the study implicates that there might be other factors affecting how female Filipinos respond to racial microaggression.